Justice Delayed is Justice Denied: An Investigation of Factors Causing Backlog of Criminal Cases in Punjab, Pakistan - Ghani, Abdul; Ayub, Zainal Amin; Mat Rus, Mukhriz (Pakistan Society of Criminology, 2023)
The backlog of criminal cases is a worrying problem in various courts in Pakistan. The backlog, in terms of years, mostly exceeds five years to fix for an appeal after the conviction at the lower court. Whilst the accused may be detained for more than five years before being brought to court for trial, the average time taken for a case from the date of the first trial up to the decision of the Supreme Court is up to 25 years. This paper seeks to identify and examine factors that contribute to the backlog of cases in the province of Punjab, Pakistan. To achieve the objective, the researcher employed a socio-legal and doctrinal methodologies that combine legal analysis and interviews with Pakistan’s criminal justice experts. Additionally, the data was collected from the office of the Regional Police Officer, Multan, Punjab Public Prosecution, Multan and District Courts of Multan from 1st January 2021 to 31st December 2021. The analysis of laws includes the interpretation and workings of the Constitution of the Republic Islamic of Pakistan (1973) and the Criminal Procedure Code (1898) which contribute to the backlog of criminal cases in the Districts Court of Multan. Based on the analysis, it is posited that the causes of backlog include poor investigation, corruption, shortages of judges, unnecessary adjournments, and an outdated criminal justice system. The backlog of cases can only be overcome if these factors are solved through various measures that involve different stakeholders